2013
DOI: 10.1631/jzus.a1200337
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the hydro-mechanical behaviour of fouled ballast

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…The tap water kept flowing into the column from the bottom and discharging from the hole on the cap of the column. This procedure lasted for at least 24 h in order to achieve moisture homogenization (Cui et al, 2013). The porosity of the specimen is 0.39.…”
Section: Materials and Preparationmentioning
confidence: 99%
“…The tap water kept flowing into the column from the bottom and discharging from the hole on the cap of the column. This procedure lasted for at least 24 h in order to achieve moisture homogenization (Cui et al, 2013). The porosity of the specimen is 0.39.…”
Section: Materials and Preparationmentioning
confidence: 99%
“…Emphasis was put on the effects of water content and fines content on the resilient modulus and permanent deformation [30]. Based on the experimental results, a constitutive model was developed, taking into account both the effect of stress level and the effect of degree of saturation [9]. Figure 10 presents typical curves of deviator stress versus axial strain for the first cycles in a test on the interlayer soil with addition of 5% subgrade soil and at 6% water content -ITL5w6 [31].…”
Section: Mechanical Behaviourmentioning
confidence: 99%
“…The results obtained in this study on the interlayer soil are in agreement with these works. To extend the model of Gidel et al [37] to the effect of water content or degree of saturation, a function relating the permanent axial strain to the water content and the applied deviator stress, t(w, q max ), was defined, as follows [29,9]:…”
Section: Mechanical Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…In the French program of conventional railway lines renewal, this interlayer with a dry unit mass as high as 2.4 Mg/m 3 (Trinh 2011) was maintained due to its favorable mechanical behavior. Thus, a series of studies have been conducted, especially on the upper part of the interlayer, aiming to clarify the effect of fines and water contents on the mechanical behavior by both monotonic and cyclic triaxial tests (Trinh et al 2012;Cui et al 2013;Duong et al 2013;Duong et al 2016;Lamas-Lopez 2016). The results showed that the increase of water content decreased the shear strength and enlarged the permanent deformation.…”
Section: Introductionmentioning
confidence: 99%